Rotational Transport of Islets: The Best Way for Islets to Get around?. (13th November 2013) - Oberhuber, Rupert; Mittermair, Christof; Zelger, Bettina; Pirkebner, Daniela; Draxl, Anna; Weissenbacher, Annemarie; Resch, Thomas; Margreiter, Christian; Sucher, Robert; Margreiter, Raimund; Pratschke, Johann; Hengster, Paul; et al.
Abstract : Islet transplantation is a valid treatment option for patients suffering from type 1 diabetes mellitus. To assure optimal islet cell quality, specialized islet isolation facilities have been developed. Utilization of such facilities necessitates transportation of islet cells to distant institutions for transplantation. Despite its importance, a clinically feasible solution for the transport of islets has still not been established. We here compare the functionality of isolated islets from C57BL/6 mice directly after the isolation procedure as well as after two simulated transport conditions, static versus rotation. Islet cell quality was assessed using real-time live confocal microscopy. In vivo islet function after syngeneic transplantation was determined by weight and blood sugar measurements as well as by intraperitoneal glucose tolerance tests. Vascularization of islets was documented by fluorescence microscopy and immunohistochemistry. All viability parameters documented comparable cell viability in the rotary group and the group transplanted immediately after isolation. Functional parameters assessed in vivo displayed no significant difference between these two groups. Moreover, vascularization of islets was similar in both groups. In conclusion, rotary culture conditions allows the maintenance of highest islet quality for at least 15 h, which is comparable to that of freshly isolated islets.